Analisis Faktor Yang Mempengaruhi Tingkat Stres Guru Di Salah Satu Sekolah Dasar Wilayah Jombang - Yani, Athi’ Linda; Retnowuni, Arifa; Asumta, Zahrul Azhar; Khusniyah, Zulfa; Zuliani, Zuliani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Work-related stress among teachers has become a critical issue in the educational sector due to its direct impact on health, productivity, and the overall quality of the learning process. This study aims to analyze the stress levels of elementary school teachers in a plus-based SD school in Jombang and to identify their implications for health and work productivity using nursing theoretical perspectives. A quantitative descriptive design was employed, involving 76 teachers as respondents. Data were collected using a questionnaire consisting of 10 items assessing stress symptoms and contributing factors. The findings revealed that 26 teachers (34.21%) experienced mild stress, 42 teachers (55.26%) experienced moderate stress, and 8 teachers (10.53%) experienced severe stress. The predominance of moderate stress indicates considerable work pressure associated with teaching demands, administrative workload, and additional responsibilities within the school. Based on nursing theories, particularly Roy’s Adaptation Model and Lazarus and Folkman’s Transactional Model, moderate to severe stress contributes to physiological and psychological maladaptation, including sleep disturbances, fatigue, reduced motivation, and early signs of burnout. Stress also significantly decreases teacher productivity, as seen in diminished teaching effectiveness, increased administrative errors, and reduced creativity. These findings highlight the urgent need for stress management strategies within schools to promote teacher health and enhance professional performance.